Implementasi Business Intelligence Dalam Menganalisis Kinerja Bisnis Virtual Hotel Operator (VHO) - Dea Prastika, Merri; Nusantoro, Jawoto; Septiani, Ana (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to present information about RedDoorz's business performance in the form of an interactive visualization dashboard that can be used as a supporting indicator for strategic decision making. This study used a descriptive exploratory approach with a Business Intelligence Roadmap development model. Data collection instruments include secondary data and literature studies, with analysis stages including business understanding, data understanding, SQL analysis, data visualization, data visualization dashboard, and user acceptance testing. The tools used in this study were Google Colab, PostgreSQL and Tableau to process, analyze and visualize data in the form of interactive dashboards. The results of the study indicate that the implementation of Business Intelligence at RedDoorz plays an important role in improving operational efficiency, supporting business planning, and strengthening competitiveness through data-based decision making and informative visualization.